Larval development of Epialtus bituperculatus H. Milne Edwards, 1834 (Crustacea: Decapoda: Brachyura: Majidae) with comments on majid larvae from the southwestern Atlantic - Negreiros-Fransozo, M. L. [UNESP]; Fransozo, A. [UNESP] (My University, 2001)
The larval development of the spider crab Epialtus bituberculatus H. Milne Edwards which lives on rocky shores with algae such as Sargassum and Hypeneia, is described. Larvae were obtained from ovigerous females collected in Ubatuba, State of São Paulo, Brazil. Rearing was carried out at 24 ± 1°C, with an average salinity of 35%. Larval development consists of two zoeal stages and one megalopa. Zoeal development was completed in 9.5 days. Analysis indicated that zoeae of E. bituberculatus are very similar to those of E. brasiliensis Dana and Acanthonyx scutiformis (Dana). Differences noted between these species pertain to the setation of the carapace, maxillule and second maxilliped. The main morphological features useful for identification are presented together with a summary of features that characterize larvae of majid subfamilies in Brazil. A key for the identification of southwestern Atlantic majid zoeae to the family level is provided.
Keywords: crab; identification key; larval development; morphology; Brazil; Decapoda; Epialtus bituberculatus; Majidae